The role of innovation in the business activity of hidden leaders of the Polish economy = Rola innowacji w działalności ukrytych liderów polskiej gospodarki - Grego-Planer, Dorota; Glabiszewski, Waldemar (Zielona Góra: Faculty of Economics and Management Press)
Globalization and internationalization of the economy compelled the implementation of innovative solutions in companies. Only those organizations that regularly implement innovations have a chance to achieve significant market positions and survive in a competitive environment. The exemplification of such highly innovative companies are H. Simon's hidden champions.
Keywords: innowacje; lider gospodarki; badania; rozwój; tajemniczy mistrzowie; innovation; leaders of economy; researches; development; hidden champions